Developing a framework for responsible innovation - Stilgoe, Jack; Owen, Richard; Macnaghten, Phil (Research Policy, 2013)
The governance of emerging science and innovation is a major challenge for contemporary democracies. In this paper we present a framework for understanding and supporting efforts aimed at ‘responsible innovation’. The framework was developed in part through work with one of the first major research projects in the controversial area of geoengineering, funded by the UK Research Councils. We describe this case study, and how this became a location to articulate and explore four integrated dimensions of responsible innovation: anticipation, reflexivity, inclusion and responsiveness. Although the framework for responsible innovation was designed for use by the UK Research Councils and the scientific communities they support, we argue that it has more general application and relevance.
Keywords: Gouvernance; Innovation responsable; Nouvelles technologies; Éthique